Elastic and thermodynamic properties of the major clinker phases of Portland cement: Insights from first principles calculations. (14th June 2021) - Mai, Ngoc Lan; Hoang, Nguyen-Hieu; Do, Ha T.; Pilz, Monika; Trinh, Thuat T.
Highlights: A systematic DFT calculations for cement clinker phases are presented. Spin-polarized treatment is crucial for ferrite structure. The calculated elastic, thermodynamic properties agree well with experimental data. More insight into the atomic charge is provided. Abstract: Portland based cement is one of the most popular materials used in the civil and construction applications. Reliable computational methods to provide an insight into the underlying mechanics of the major phases of this material are of great interest for cement design. The present work investigated the performance of density functional theory (DFT) calculations using the PBE-D2 method to predict the mechanical, thermodynamic properties of four major phases namely Alite C3 S, Belite C2 S, tricalcium aluminate C3 A and tetracalcium aluminoferrite C4 AF. The calculated elastic properties were in a good agreement with available experimental data. In addition, a deeper insight into the electron density of state, spin-polarization, atomic charge, as well as free energy and entropy properties were also presented. Further development is necessary to improve the established DFT models for predicting the mechanical properties of the ferrite phase of Portland clinker.